2012
DOI: 10.1097/scs.0b013e318232a7aa
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction for Defects of the Lower Lip After Tumor Ablation

Abstract: Successful reconstruction of all defects can be attained, if as many surgical procedures as possible have been mastered, and a more proper means used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Our patient has not experienced any difficulty in phonation or lip incompetence up to three-month postoperative follow-up. The integrity of the muscle function after the surgery has been well documented in a previous study by Zhai et al17. As demonstrated by our case, restoration of adequate lip function and its natural positioning traditionally embodies a two-stage procedure with the commissuroplasty step performed three weeks after the flap insetting, although a handful of authors have reported success with single-stage techniques1819.…”
Section: Discussionsupporting
confidence: 71%
“…Our patient has not experienced any difficulty in phonation or lip incompetence up to three-month postoperative follow-up. The integrity of the muscle function after the surgery has been well documented in a previous study by Zhai et al17. As demonstrated by our case, restoration of adequate lip function and its natural positioning traditionally embodies a two-stage procedure with the commissuroplasty step performed three weeks after the flap insetting, although a handful of authors have reported success with single-stage techniques1819.…”
Section: Discussionsupporting
confidence: 71%
“…13 Lower lip defects more than 2/3 and central defects can also be reconstructed with Webster-Bernard technique, Gillies fan flap and Abbe-Estlander flap, or even the radial forearm free flap and the anterolateral thigh free flap. 4,14 However, a variety of shortcomings had been noted in surgical approach to repairing larger lower lip defects, and there is no consensus regarding which techniques are the best. Abbe flap needs the secondary surgery for pedicle division of flap and the surgical procedure is relatively complex and time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Abbe flap, Karapandzic flap, Estlander flap, Bernard–Webster flap, and other various modified flaps are some of the techniques currently used 13 . Lower lip defects more than 2/3 and central defects can also be reconstructed with Webster–Bernard technique, Gillies fan flap and Abbe–Estlander flap, or even the radial forearm free flap and the anterolateral thigh free flap 4,14 . However, a variety of shortcomings had been noted in surgical approach to repairing larger lower lip defects, and there is no consensus regarding which techniques are the best.…”
Section: Discussionmentioning
confidence: 99%
“…Lip cancer has been described by some authors as one of the most common head and neck cancers, compromising approximately 25-35% of all cases in this region 24 . In this study, lip cancer was the second most frequent, affecting 14.8% of all cases, which might be explained by our geographic region, skin colour, and frequent sun exposure, as one of the main aetiological factors of lip cancer is longterm exposure to ultraviolet (UV) radiation and fair skin 25 .…”
Section: Discussionmentioning
confidence: 99%